INTEGRATION OR INCLUSION? CHALLENGES OF THE INCLUSIVE PHYSICAL EDUCATION (Fiep Bulletin - online, 2015)
The proposal of this essay is to present the discussions accomplished by the group of study Activity Physical Inclusion Exclusion, of the program of master's degree of the Universidade Salgado de Oliveira/UNIVERSO. The work it inserts in the line of research Physical Activity, Culture and Society, discussing the origin of the inclusive education, the normalization principles and of inclusion and the relationship with the ideas of to integrate and to include. Besides, it intertwines the debate between competition and cooperation of form contextualized, looking for a link for the active and critical learning. They come some proposed that can contribute for the development of an inclusive physical education.
Keywords: inclusive physical education; inclusion; exclusion.